Relationship between kidney function and healthy life expectancy: A historical cohort study - Hisayuki Ogura; Tadashi Toyama; Hikaru Samuta; Kohei Hirako; Tomoya Itatani; Shiori Nakagawa; Megumi Oshima; Shinji Kitajima; Akinori Hara; Norihiko Sakai; Miho Shimizu; Tomoyuki Takura; et al. (BMC Nephrology)
Abstract Background The impact of chronic kidney disease (CKD) on healthy life expectancy and healthcare costs requires research. This study examined associations between CKD and healthy life expectancy, and its economic burden. Methods This study of community-dwelling adults residing in Hakui City, Ishikawa Prefecture, Japan used data from the National Health Insurance database between 2012 and 2022. Participants were grouped by baseline estimated glomerular filtration rate (eGFR) (< 45, ≥ 45 to < 60, ≥60 to < 75, ≥75 to < 90, and ≥ 90 mL/min/1.73 m²). The primary endpoint was a composite of becoming a care level ≥ 2 or death. Multivariable Cox proportional hazards models were used to calculate the risk regarding time to the primary endpoint. Secondary endpoints were the annual medical and long-term care costs. Results The 5,592 participants had a mean follow-up of 6.4 years. The hazard ratio was 1.86 (95% confidence interval [CI]: 1.35 to 2.55) for the eGFR < 45 group and 1.60 (95% CI: 1.13 to 2.25) for the eGFR ≥ 90 group, both compared with the eGFR ≥ 60 to < 75 group. Both annual costs were significantly higher in the lower eGFR groups than in the higher eGFR groups. For the eGFR < 45 group, the median medical care cost was 0.38 million yen/year in all participants and the median long-term care cost was 0.40 million yen/year in primary endpoint achievers. A lower eGFR was correlated with longer unhealthy years of life. Conclusions Higher and lower eGFRs were associated with increased risks of reduced healthy life expectancy. A lower eGFR was associated with higher medical and long-term care costs.